Effect of sulfonation density on acid strength in ion exchange resins: Insights from solid-state NMR and density functional theory - Tumulu, Goutam Narayan; Datar, Sarvesh; Shelke, Ankita; Swain, Gitanjali; Ajithkumar, T. G.; Thirumalaiswamy, Raja; Mohan, Ojus; Mahajani, Sanjay M. (Molecular Catalysis, 2026)
Ion-exchange (IE) resins are widely used as solid acid catalysts; however, their surface acidity remains poorly characterized because their limited thermal stability precludes conventional NH3-based acidity measurements. Moreover, acid-site accessibility in IE resins is strongly governed by solvent- or reactant-induced swelling. Here, we investigate the surface acidity of commercial Amberlyst and Indion IE resins using & sup3;& sup1;P MAS NMR (Magic Angle Spinning Nuclear Magnetic Resonance), employing TMPO as a molecular probe dispersed on the resin with moderately swelling dichloromethane, thereby capturing the swollen-state acidity relevant for predicting catalytic activity. The deconvolution of the P-31 MAS NMR spectra reveals three distinct acid-strength zones arising from inhomogeneous sulfonation of the polymer matrix. The overall acidity, quantified by the area-weighted average P-31 chemical shift (delta), increases monotonically with sulfonation density. Notably, only resins containing acid sites stronger than similar to 80 ppm exhibited measurable catalytic activity in alpha-pinene isomerization, establishing a direct correlation between acidity and activity. Density functional theory (DFT) calculations on representative resin models, supported by electron-density analyses, attribute the enhancement of acid strength at higher sulfonation densities to cooperative hydrogen-bonding networks among neighboring sulfonic acid groups. Together, these findings establish P-31 MAS NMR-derived surface acidity as a catalytically relevant descriptor for the rational selection of IE resins in liquid phase acid-catalyzed chemistries.
Keywords: Acid strength; Density functional theory; heterogeneous catalysis; Ion-exchange resins; Solid acids; Solid-state NMR